2018
DOI: 10.5093/pi2018a5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Positive Youth Development: A Psychosocial Intervention Evaluation

Abstract: Initial evidence of the effectiveness of positive youth development (PYD) programs in promoting positive change in concepts and constructs related to positive identity has led to an interest in developing, implementing, and evaluating interventions that specifically target core components of identity formation in adolescents as a strategy for promoting positive outcomes and preventing negative outcomes. The potential utility of interventions that target identity formation has also been discussed extensively wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
9
0
1
Order By: Relevance
“…Future studies should examine mechanisms that may be involved in this process. Additionally, campaigns aimed at training parents as psychosocial protective agents against adolescent aggressiveness, such as, for example media campaigns or family programs, should be informative (Cornelius, Earnshaw, Menino, Bogart, & Levy, 2017;Rinaldi & Farr, 2018). Specifically, interventions with aggressive adolescents and their parents should be focused on fostering a warmth relationship within the family, based on dialogue and affection, helping the aggressive adolescents to improve their family perceptions, as valued and appreciated members in home.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine mechanisms that may be involved in this process. Additionally, campaigns aimed at training parents as psychosocial protective agents against adolescent aggressiveness, such as, for example media campaigns or family programs, should be informative (Cornelius, Earnshaw, Menino, Bogart, & Levy, 2017;Rinaldi & Farr, 2018). Specifically, interventions with aggressive adolescents and their parents should be focused on fostering a warmth relationship within the family, based on dialogue and affection, helping the aggressive adolescents to improve their family perceptions, as valued and appreciated members in home.…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that the causal paths for the specific outcomes were moderated by gender and ethnicity via their effects on mediators (i.e., identity processes) rather than through direct effects on outcomes. In the process of self‐construction and self‐discovery during emerging adulthood, PYD interventions should promote equal opportunities for both genders to thrive by progressive cascading effects on behavior problems that operate through effects on positive outcomes (Eichas, Kurtines, Rinaldi & Farr, ).…”
Section: Discussionmentioning
confidence: 99%
“…MBT is meant to be a therapeutic “stance” rather than a strictly manualized treatment (Bateman & Fonagy, 2012). Due to this flexibility, it may be possible to incorporate RF‐promoting strategies from MBT into existing interventions for building healthy identity during adolescence, such as the Miami Youth Development Project (Kurtines et al, 2008) and the Changing Lives Program (Eichas, Kurtines, Rinaldi, & Farr, 2018), among others (see Ferrer‐Wreder, Montgomery, Lorente, & Habibi, 2014). Further, given similarities between RF and social‐cognitive constructs such as metacognition and theory of mind, promoting these abilities in the context of existing identity interventions may also be beneficial.…”
Section: Discussionmentioning
confidence: 99%